Features of the classification of acrobatic exercises of group B - "balancing" and their varieties in artistic swimming - Petrenko, A.; Kamaiev, O. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to classify acrobatic exercises of group B according to their level of complexity.